PROFIL GEN GROWTH HORMONE (GH) SAPI HASIL PERSILANGAN MADURA DAN LIMOUSIN DENGAN METODE PCR-RFLP - Puteri, Ghea Aquatica; Utomo S, Budi; Darsono, Roesno (Universitas Airlangga, 2019)
The purpose of this research was to find out the Growth Hormone (GH) gene profile of the cross breeding between Madura cattle and Limousin cattle (Madrasin). Sampl in the form of cattle blood for this research was obtained from 14 Madrasin cattles in the area of Bangkalan, Madura, East Java. DNA extraction was performed then to provide the result for PCR RFLP, which then indicated that Madrasin cattle's GH gene profile has 432 base pair fragment length and the RFLP result indicated that Madrasin cattle's GH genetic was cut off into 180 base pair, 250 base pair, 300 base pair, and 400 base pair. Moreover, there was no V genetic to be found in GH genetic of Madura cattle.